Conservative treatment approach with botulinum toxin for cases of asymptomatic hypertrophy of the masseter muscle (Research, Society and Development, 2020)
Commonly related to parafunctional habits, Masseteric Hypertrophy represents an asymptomatic increase of the lower third of the face. Without gender preference, it has been shown to be prevalent in the second and third decades of life. As an alternative to surgical treatment, the use of Botulinum Toxin A has been increasingly effective in desired clinical results, such as reduced muscle thickness. This study aims to report the case of application of Botulinum Toxin A in an asymptomatic patient who presented bilateral hypertrophy of the masseter muscle, with 120 days follow-up of application where we observed improvement in facial aesthetics due to the reduction in volume of the muscles.